Estimating the mechanical anisotropy of the Iranian lithosphere using the wavelet coherence method - Zamani, A.; Samiee, J.; Kirby, Jonathan (Elsevier Science BV, 2013)
We calculated anisotropic wavelet coherence between Bouguer anomaly and topography in order to map the anisotropy of the effective elastic thickness of the Iranian lithosphere (Te). An orthotropic elastic plate model is used for inverting the anisotropic wavelet coherence to compute the mechanical anisotropy through the weak axis of the Te. Anisotropy of the Te-weak axis and the strength of the anisotropic parameter, namely the anisotropic coherence effect over the study area are estimated by restricting the rotated Morlet wavelet (fan wavelet) geometry over an azimuthal range of 90°. Large-scale Te variations have been shown to be associated with phenomena, such as mountain belts, subduction zones, craton boundaries, fault zones, and seismogenic regions. Although the correlation between the major tectonic features of the Iranian lithosphere and the distribution of the Te-weak axis is not general or precise, in some regions, such as the Central Iran Blocks, and the Alborz, Kopeh Dagh, Zagros, and Makran orogenic belts, the weak axis has a uniform or slowly varying pattern which changes over their boundaries. A perpendicular alignment between seismic anisotropy measurements in Iran and the Te-weak directions suggests a lithospheric origin for anisotropy. The correlation between averaged stress directions and the weak axis of the Te in Iran indicates that the present day stress field and the fossil strain are still related. Correlation between these factors suggests vertically coherent deformation of the lithosphere in Iran resulting from the multiply convergent orogenic processes. The complex mechanical anisotropy pattern of the Iranian lithosphere results from the interaction of many pre-existent structures which dominantly control the mechanical anisotropy of the lithosphere.